2019
DOI: 10.1038/s41467-019-08909-4
|View full text |Cite
|
Sign up to set email alerts
|

Urban pollution greatly enhances formation of natural aerosols over the Amazon rainforest

Abstract: One of the least understood aspects in atmospheric chemistry is how urban emissions influence the formation of natural organic aerosols, which affect Earth’s energy budget. The Amazon rainforest, during its wet season, is one of the few remaining places on Earth where atmospheric chemistry transitions between preindustrial and urban-influenced conditions. Here, we integrate insights from several laboratory measurements and simulate the formation of secondary organic aerosols (SOA) in the Amazon using a high-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
186
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(194 citation statements)
references
References 106 publications
6
186
0
2
Order By: Relevance
“…At the same time, NO x had little effect on the mass concentration of SOA. Other studies, on the other hand, indicate a strong increase in biogenic SOA due to NO x (e.g., Shrivastava et al, ). It is possible that organonitrate HOMs (HOM‐ONs), which are formed from biogenic vapors in the presence of NO x , are much less efficient in forming particles than other HOMs (Lehtipalo et al, ), probably due to their higher volatilities, but they might still be efficient in the aerosol growth.…”
Section: Nucleation and Growth Mechanisms: New Results From Laboratormentioning
confidence: 93%
See 1 more Smart Citation
“…At the same time, NO x had little effect on the mass concentration of SOA. Other studies, on the other hand, indicate a strong increase in biogenic SOA due to NO x (e.g., Shrivastava et al, ). It is possible that organonitrate HOMs (HOM‐ONs), which are formed from biogenic vapors in the presence of NO x , are much less efficient in forming particles than other HOMs (Lehtipalo et al, ), probably due to their higher volatilities, but they might still be efficient in the aerosol growth.…”
Section: Nucleation and Growth Mechanisms: New Results From Laboratormentioning
confidence: 93%
“…Tröstl et al (2016) showed that GR of 5 to 50 nm particles cannot be explained by HOMs alone, suggesting that LVOCs that are not measured by the nitrate-CIMS and some additional SVOCs may be also involved in the growth. Hao et al (2009) Shrivastava et al, 2019). It is possible that organonitrate HOMs (HOM-ONs), which are formed from biogenic vapors in the presence of NO x , are much less efficient in forming particles than other HOMs , probably due to their higher volatilities, but they might still be efficient in the aerosol growth.…”
Section: Homs Formed From Vocs Oxidation Reactionsmentioning
confidence: 99%
“…The dependence of OH on NO 2 concentrations inferred from the analysis in Figure is consistent with several previous observations, including the Tropospheric OH Photochemistry Experiment (Eisele et al, ), measurements made during the Biosphere Effects on Aerosols and Photochemistry Experiment II (BEARPEX09) (Mao et al, ), measurements made at a ground site during the SENEX study (Feiner et al, ), and with the OH dependence on NO 2 predicted from well‐known chemical reactions in the troposphere (McKeen et al, ). Indirect evidence for increased oxidation rates of VOCs at enhanced NO x concentrations was obtained downwind from Manaus in the Amazon during GoAmazon2014/5 (Shrivastava et al, ). Our analysis does not provide evidence for higher than expected OH concentrations at lower NO x concentrations as suggested by the recent summary of OH measurements (Rohrer et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…δ-limonene is the most emitted monoterpene (45%), followed by trans-β-ocimene (18%) and α-pinene (17%). NO soil emissions are also accounted for with a constant flux of 8.3×10 9 molec cm −2 s −1 following Shrivastava et al (2019).…”
Section: Biogenic Emissionsmentioning
confidence: 99%
“…Koss et al, 2017a, b), such 50 measurements are not available for the GoAmazon 2014/5 campaign. 3D models that were run for the Manaus situation offer an anonymized view of SOA composition (Shrivastava et al, 2019) because they rely on a Volatility Basis Set parameterization (VBS, Donahue et al, 2006). The Generator for Explicit Chemistry and Kinetics of Organics in the Atmosphere (GECKO-A, Aumont et al, 2005;Camredon et al, 2007) is the ideal tool to model atmospheric organic chemistry with a detailed molecular view.…”
mentioning
confidence: 99%